Rehabilitation in Triangular Fibrocartilage Complex Injuries: Treatment Algorithm - Eva Guisasola Lerma; Francisco Javier Lucas Garcia; Alberto Márquez Caraballo; David Santosjuanes Royo (Revista Iberoamericana de Cirugía de la Mano, 2022)
Injuries to the triangular fibrocartilage complex (TFCC) can lead to instability of the distal radioulnar joint (DRUJ). In fact, they are the most frequent cause of it. But, in other cases, depending on the type of injury, the DRUJ remains stable. This will condition different types of treatments, from conservative management to the different options of surgical treatment. Since a controversy persists regarding the management of these lesions, our purpose is to disclose the foundations of the rehabilitation treatment and propose an algorithm of treatment according to the different types of injuries and their repairs.